2018
DOI: 10.3389/feart.2018.00227
|View full text |Cite
|
Sign up to set email alerts
|

Droughts Over Amazonia in 2005, 2010, and 2015: A Cloud Cover Perspective

Abstract: Amazon forests experienced recent severe droughts in an anomalous short period induced by different mechanisms and had different length periods and spatial patterns. Droughts of 2005 and 2010 were attributed to anomalous Sea Surface Temperature (SST) over the Tropical North Atlantic (TNA) during the dry season, but the 2010 drought was more severe and remained for a longer period because it was also induced in late 2009 by a moderate to strong El Niño (EN). Drought in 2015 led to unprecedented warming and extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 29 publications
1
19
0
1
Order By: Relevance
“…At the threemonthly time scale, the magnitude of surface warming was repeated spatially, since more than half of the Brazilian Amazon experienced significant positive temperature anomalies, during the last two trimesters of 2015 and first of 2016, corroborating and adding to the results presented by Jiménez-Muñoz et al (2016). This anomalous surface warming can be explained by an increase in the direct solar radiation reaching the land surface (Anderson et al, 2010), resulting from a drastic reduction in cloud cover during extreme droughts in Amazonia (Jimenez et al, 2018;Martins et al, 2018). According to Jiménez-Muñoz et al (2016), anomalous surface warming combined with reduced rainfall can increase drought severity by 20% in the Amazon, due to the increase in potential evapotranspiration.…”
Section: Discussionmentioning
confidence: 62%
“…At the threemonthly time scale, the magnitude of surface warming was repeated spatially, since more than half of the Brazilian Amazon experienced significant positive temperature anomalies, during the last two trimesters of 2015 and first of 2016, corroborating and adding to the results presented by Jiménez-Muñoz et al (2016). This anomalous surface warming can be explained by an increase in the direct solar radiation reaching the land surface (Anderson et al, 2010), resulting from a drastic reduction in cloud cover during extreme droughts in Amazonia (Jimenez et al, 2018;Martins et al, 2018). According to Jiménez-Muñoz et al (2016), anomalous surface warming combined with reduced rainfall can increase drought severity by 20% in the Amazon, due to the increase in potential evapotranspiration.…”
Section: Discussionmentioning
confidence: 62%
“…It has been rarely considered as a variable, and few works have shown its importance in drought. As an example, Jimenez et al [58], in their study on droughts in the Amazonia region, analyzed its importance and found it to be a significant factor, owing to the long-term land use, land-cover change and forest loss in the region. Similarly, vapor pressure has shown a strong correlation with the water transport process in various vegetation types.…”
Section: Training Periodmentioning
confidence: 99%
“…The study area is a large area of the Amazon forest. The Amazon forest is a tropical ecosystem characterized by wet conditions; however, it has experienced recurrent and large-scale droughts over the last few years [44,45]. The extreme drought events occurring in 2005, 2010, and 2015 were induced by different large-scale atmospheric mechanisms associated with warm sea surface temperatures (SST).…”
Section: The Study Areamentioning
confidence: 99%
“…The 2005 and 2010 drought conditions are attributed to warm SSTs over the Atlantic (Atlantic Multidecadal Oscillation, AMO) inducing the contraction of the northeast trade winds and moisture flux from the warming Tropical North Atlantic (TNA) SST. On the other hand, the 2015 drought event is attributed to the warm SSTs over the tropical Pacific (to El Niño-Southern Oscillation, ENSO) [44,46,47].…”
Section: The Study Areamentioning
confidence: 99%